2012
DOI: 10.3109/01913123.2012.681833
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Multiplicity Is an Independent Prognostic Factor of Non-muscle-invasive Bladder Cancer Treated with Bacillus Calmette-Guerin Immunotherapy

Abstract: Significant independent predictor for recurrence was multiplicity which offers important clinical information and may be a useful tool in the selection of suitable candidates for BCG-immunotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…We first observed that treatment outcome was influenced by age, treatment scheme and tumour multifocallity, as showed in other reports (Bohle and Bock, 2004; Joudi et al , 2006; Fernandez-Gomez et al , 2008; Malmstrom et al , 2009; Kohjimoto et al , 2010; Ajili et al , 2012). To overcome the samples heterogeneity, these variables were taken into account in multivariate analysis models to assess the influence of tumour-associated glycans in BCG response.…”
Section: Discussionsupporting
confidence: 59%
“…We first observed that treatment outcome was influenced by age, treatment scheme and tumour multifocallity, as showed in other reports (Bohle and Bock, 2004; Joudi et al , 2006; Fernandez-Gomez et al , 2008; Malmstrom et al , 2009; Kohjimoto et al , 2010; Ajili et al , 2012). To overcome the samples heterogeneity, these variables were taken into account in multivariate analysis models to assess the influence of tumour-associated glycans in BCG response.…”
Section: Discussionsupporting
confidence: 59%
“…38 Although not specific to patients with IR disease, a more recent retrospective analysis examining the clinical and pathologic data of 112 patients with primary NMIBC treated with TURBT and BCG found tumor multiplicity to be the only independent predictor of disease recurrence. 39 …”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies (10 of 12) investigated the associations of smoking status with disease recurrence [11][12][13][14][15][16]17 19,20]. Attributable to variations in the study sample sizes, there were variations of the comparator groupings.…”
Section: Impact Of Smoking On Outcomesmentioning
confidence: 97%
“…To summarize the best available evidence, we selected 12 studies that met the inclusion criteria for this review article of which five studies were published prior to 2011. The associations of smoking with disease recurrence and progression, the two most important disease outcomes in NMIBC, are summarized in Table 1 [11][12][13][14][15][16][17][18][19][20][21][22]. Although there are minor variations in disease outcome definitions among studies, the definitions were sufficiently similar to allow for evidence synthesis.…”
Section: Impact Of Smoking On Outcomesmentioning
confidence: 98%